Аnalysis Direct Results of Reconstructive Interventions on the Mitral and Tricuspid Regurgitation Resulting from Dilated Cardiomyopathy - Rudenko, K.; Krykunov, A.; Buriak, R. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The basis of the study were 54 patients with mitral and tricuspid regurgitation resulting from dilated cardiomyopathy who were on the examination and surgical treatment to the National Institute of Cardio-vascular surgery named after M.M. Amosov from 01.01.2007 to 01.01.2015 years. The average age of patients was 50±14 years. The research was the identification of statistically significant changes end-diastolic and end-systolic index, left ventricular ejection fraction in the pre- and post-operative treatment of patients with mitral and tricuspid regurgitation resulting from dilated cardiomyopathy.